Strategi Pengendalian Dan Pemberian Fasilitas Kepada Penanam Modal Asing Di Kawasan Ekonomi Khusus Indonesia Sebagai Bentuk Controls By The Host State - Bana, Muhammad Hasan Al (Universitas Sang Bumi Ruwa Jurai, 2024)
One of the Indonesian Government's strategies to attract foreign investors is to prepare certain areas that have potential strategic advantages from a geographical and geostrategic perspective through Special Economic Zones (KEK). Therefore, the formulation of this research problem is: What form of control does Indonesia have as a Host State that can attract foreign investors to invest their capital in Special Economic Zones? And what are the policies and facilities provided by the government in Special Economic Zones to attract foreign investors? This research discusses the form of control of Indonesia as a host state in order to attract foreign investors to invest in Special Economic Zones, then also discusses the policies and facilities provided by the government in special economic zones to attract foreign investors. The conclusion of this research is that the control of a Host State regarding foreign investment must have a legal umbrella that can provide a basis for every foreign investment activity in Indonesia. One form of controlling Indonesia as a Host State in foreign investment activities is by providing incentives and facilities in Special Economic Zones